6. The Number of Erythrocytes and Hematocrit Value of Broilers that Infected by Eimeria tenella And Given Neem Leaf Extract Combined With Jaloh Extract - Rizki Putra; Sugito Sugito; Zuhrawaty Zuhrawaty; M. Hasan; Rusli Rusli; Abdullah Hamzah; Rosmaidar Rosmaidar; Herrialfian Herrialfian (Universitas Syiah Kuala, 2020)
This research aim was to determine the number of erythrocytes and hematocrit value of broilers that infected by Eimeria tenella and given neem leaf extract combined with jaloh extract. Sample used in this study is 20 strains Cobb broiler chickens aged 15 days old. Sampled broilers were separated into 5 treatment groups consisting of 4 chickens, each treatment were chicken that infected by oocysts Eimeria tenella and not given other treatments (P1), chicken infected by oocysts Eimeria tenella and given the anti-stress commercial (P2), chicken infected by oocysts Eimeria tenella and given the leaf extract jaloh 1000mg/L (P3), chicken infected with oocysts Eimeria tenella and given extracts of neem leaf 250mg/L (P4), and a chicken infected with oocysts Eimeria tenella and given the leaf extract jaloh 1000mg/L combined with neem leaf extract 250mg/L (P5). Administration of each treatment were dissolved into the chicken water and administered for 10 days in the morning and evening. The design used in the study was completely randomized design with 5 treatments, each treatment consisted of 4 repetitions. Parameters observed were the number of erythrocytes and hematocrit values. Results from this study showed that neem extracts combined with jaloh given for 10 days had no effect on the number of erythrocytes and hematocrit values of broilers that infected by Eimeria tenella